Analysis of Critical Activity in the Hydromechanical Component Fabrication Project for Dam “X” using the Critical Path Method - Pramudi Arsiwi; Tita Talitha; Dony Satriyo Nugroho; Maharsa Pradityatama (OPSI, 2023)
One of the projects currently being undertaken by PT. XYZ is Dam “X”. Based on project management data obtained from PT. XYZ, the actual project construction process experienced a significant delay from the planned schedule, with a delay duration of approximately 30 days. The delay will have an impact on the duration of the final completion of the project, including the process of delivering project results to consumers. The purpose of this study is to determine the critical path in project implementation and identify activities that do not have slack time because it will affect the duration of the overall project completion. The method used in this study is the Critical Path Method (CPM), which is a network method consisting of a series of activity components with the longest total time and showing the fastest duration of project completion. The results showed that the Manufacturing Project has a total of 11 critical activities out of 37 activities (work packages), with a total critical time of 75 days. The total critical time from the calculation of the CPM method also shows the optimal total project duration which can be used as a reference for the project team for the completion of a fabrication project or a hydromechanical component installation project on Dam "X".